New product forecasting: Methods - Karima Dyussekeneva (LAP LAMBERT Academic Publishing, 2012)
This book investigates three approaches to new product sales forecasting:statistical, judgmental and the integration of these two approaches. The aim of the bookis to find a simple, easy-to-use, low cost and accurate tool which can be used bymanagers to forecast the sales of new products. A review of the literature suggested thatthe Bass diffusion model was an appropriate statistical method for new product salesforecasting. For the judgmental approach, after considering different methods andconstraints, such as bias, complexity, lack of accuracy, high cost and time involvement,the Delphi method was identified from the literature as a method, which has thepotential to mitigate bias and produces accurate predictions at a low cost in a relativelyshort time. However, the literature also revealed that neither of the methods: statisticalor judgmental, can be guaranteed to give the best forecasts independently, and acombination of them is the often best approach to obtaining the most accuratepredictions.The study in this book compares these three approaches by applying them toactual sales data. To forecast the sales of new products, the Bass diffusion model wasfitted to the sales history of similar (analogous) products that had been launched in thepast and the resulting model was used to produce forecasts for the new products at thetime of their launch. These forecasts were compared with forecasts produced throughthe Delphi method and also through a combination of statistical and judgmentalmethods. All results were also compared to the benchmark levels of accuracy, based onprevious research and forecasts based on various combinations of the analogousproducts’ historic sales data. Although no statistically significant difference was foundin the accuracy of forecasts, produced by the three approaches, the results were moreaccurate than those obtained using parameters suggested by previous researchers.